If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -44 = 6(x + -1) + -4 Combine like terms: 16 + -44 = -28 -28 = 6(x + -1) + -4 Reorder the terms: -28 = 6(-1 + x) + -4 -28 = (-1 * 6 + x * 6) + -4 -28 = (-6 + 6x) + -4 Reorder the terms: -28 = -6 + -4 + 6x Combine like terms: -6 + -4 = -10 -28 = -10 + 6x Solving -28 = -10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -28 + -6x = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 -28 + -6x = -10 + 0 -28 + -6x = -10 Add '28' to each side of the equation. -28 + 28 + -6x = -10 + 28 Combine like terms: -28 + 28 = 0 0 + -6x = -10 + 28 -6x = -10 + 28 Combine like terms: -10 + 28 = 18 -6x = 18 Divide each side by '-6'. x = -3 Simplifying x = -3
| d=h-64 | | 7*ex=14 | | 22w=15 | | 5(8m+8)=-6(8+8m) | | 3p(p+5)=0 | | 1-3m=1-7m | | 7ex=14 | | 2(x-4)+3x=12 | | 7x-(2x-4)=19 | | 7(4x+6)=-6(1-6x) | | 12.5y=225 | | 6(5p+8)=4(4+8p) | | x^2+13+42= | | 13+8x=x+6 | | 3x^2+30x=72 | | 15x^5-2x^3=24 | | 7x+1=-11+4x | | -x=0.75 | | B(t)=10et | | 11+8x=10x-3 | | -3(1+4p)=69 | | 3x(a-2b)+3b= | | -124=-2p+4(2-5p) | | 8a+3=6a+2 | | -124=2p+4(2-5p) | | 20=5b+8-b | | 2b+7b=9 | | 7u+49=-5u+25 | | X^2y-3xy^2-6x^2y= | | x+2/5+x=2/3 | | 8x-4+3x=8x+14 | | a^2+2a-1=0 |